Triangle Velocity Analysis of the Pelton Turbine Design in Microhydro Power Plant - Setiawan, Dibyo; Yowando Putro Wicaksono; Herbert Hasudungan Siahaan; Cahyo Wibowo; Fisika Prasetyo Putra (Jurnal Konversi Energi dan Manufaktur, 2025)
During the period of 29 years, the Central Java Provincial Government has implemented strategic research formulation for flood reduction efforts. One solution for flood management is building a dam. The built dam has the potential to generate electricity. The purpose of the activity is to analyze the turbine speed triangle from the results of the technical design. The method used is the analysis of the turbine speed triangle at an entry angle of 12-14°. The results of the triangle analysis obtained show the F value at 14-12° of 34695.5, 34761.6, and 34847.7 N.m. Torque at 14° were 5313, 5320, and 5330 N.m. Torque at 13° were 5363, 5370, and 5380 N.m. Torque 12° were 5401, 5409, and 5418 N.m. P at 14-12° were 641.5, 642.9, and 644.1 kW. The efficiency of ηo and ηm is 0.90 % and 0.95 %. The conclusion of the application of the turbine speed triangle analysis at an angle of 4-6° is that the optimum turbine efficiency is at an opening angle of 12° with the ability to increase turbine power by 14.79 % and efficiency by 14.66 %.